Resíduo seco de mandioca na alimentação de frangos de corte - Trautenmüller, Heloíse (2016)
The objective of this study was to evaluate the effects of different levels of inclusion of cassava starch residue (CSR) on the energy situation, the intestinal villi, performance and broiler carcass yield 1-42 days old. For the assessment of energy metabolism values were two test periods on 11-21 days and 31-41 days of age. The birds were housed in metabolic cages equipped with feeders and drinkers, being used 250 chicks in the first experiment and 125 broilers in the second experiment. The experiments lasted 10 days, five days for adaptation and five days to collect feces, which were held in a range of 12 hours. The RSM was obtained from a tapioca starch industry and dried under pressure 9 kg h-1 for 15 to 20 minutes, analyzes were made of the chemical composition of the waste resulting in 1.12% of crude protein (CP), 0, 31% ether extract (EE), 3600 kcal kg -1 gross energy (GE), 38.22% of neutral detergent fiber (NDF), 20.82% of acid detergent fiber (ADF), 13.57% of crude fiber (CF) and 60.73% of starch. The birds were placed in a completely randomized design with four experimental diets and a reference diet with four repetitions in the first experiment and five replications in the second experiment. CSR replaced by 10, 20, 30 and 40% of maize basal diet. Data were submitted to polynomial regression analysis on the basis of RSM levels, excluding the control diet (0% CSR). Levels of dry cassava did not influence (P> 0.05) the apparent metabolizable energy (AME), apparent metabolizable energy corrected for nitrogen balance (AME), metabolization coefficient of gross energy (MC) and coefficient metabolization of gross energy corrected for nitrogen balance (MCn) in any of the evaluated phases. For the methodology Adeola (2001) AMEn for the period 11 to 21 days it was 1534 kcal kg-1 and 31 to 41 days it was 1746 kcal kg-1. To evaluate the effects of CSR on the performance of birds, were used 980 chicks, males, Cobb Slow, housed in brick shed, equipped with feeders, drinkers, nipple type, and floor covered with wood shavings. Birds were allocated in a completely randomized design with seven treatments (0, 2, 4, 6, 8, 10 and 12% of CSR) and seven replicates and 20 birds per experimental unit. They evaluated the weight gain, feed intake, feed conversion, carcass yield, the commercial cuts and intestinal morphology. In the period from1 to 7 days the weight gain (WG) and feed conversion (FC) had a quadratic effect with the largest weight found in the level of 9.55%and higher FC level of 6.67% of inclusion and up to 6%ofinclusiondid not differ (P<0.01) than the control treatment. From 1to 21 days the WG reduced linearly with increasing inclusion of CSR while FC increased linearly, and up to 6% inclusion the WG did not differ (P <0.01) than control treatment and up to 8% FC did not differ from control treatment. In carcass yield analysis was no effect (P<0.01) for breast yield (BRES) linearly decreased as the increase of CSR inclusion levels. The crypt depth (CRY) increased linearly as the inclusion of CSR. According to the data found the dry cassava can be included in up to 6% substitution in the feed of broilers in the period1-42days of age without impairing the performance of the birds